Collaborative Governance in Ecological Politics: Non-Govermental Organization Influence and Strategies in Food Estates Program in Central Kalimantan - Asep Hendra; Ismunarta Ismunarta (Politicon : Jurnal Ilmu Politik, 2024)
This study explores the role of NGOs in the governance of food estate projects in Central Kalimantan, Indonesia. The food estate program aims to boost national food production but faces significant environmental and social challenges due to its implementation on fragile peatland ecosystems. Past projects have led to severe environmental degradation and social conflicts, raising concerns about the sustainability and inclusiveness of the current initiative. Using a qualitative research approach, this study analyzes how NGOs influence food estate policies and their strategies for promoting good environmental governance. Data collection involved semi-structured interviews with stakeholders, field observations, and document analysis. The findings reveal that NGOs significantly impact policy formulation and implementation by providing scientific data, advocating for community rights, and ensuring independent oversight. Their involvement enhances policy effectiveness, promotes sustainability, and fosters social equity, highlighting the importance of collaborative governance in addressing complex environmental and social issues